2020
DOI: 10.1039/c9cc09598e
|View full text |Cite
|
Sign up to set email alerts
|

Visible photorelease of liquid biopsy markers following microfluidic affinity-enrichment

Abstract: We detail a heterobifunctional, 7-aminocoumarin photocleavable (PC) linker with unique properties to covalently attach Abs to surfaces and subsequently release them with visible light (400–450 nm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…The attractive nature of this design is that it can process whole blood directly yielding high recovery of CTCs with high purity . The selection module was replicated in COC because this material has excellent optical properties that enable efficient UV/O 3 activation of the high-aspect-ratio microchannels for high loads of antibody onto the activated channels using the PC linker as well as high transmissivity in the blue region of the electromagnetic spectrum to allow for efficient CTC release …”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The attractive nature of this design is that it can process whole blood directly yielding high recovery of CTCs with high purity . The selection module was replicated in COC because this material has excellent optical properties that enable efficient UV/O 3 activation of the high-aspect-ratio microchannels for high loads of antibody onto the activated channels using the PC linker as well as high transmissivity in the blue region of the electromagnetic spectrum to allow for efficient CTC release …”
Section: Resultsmentioning
confidence: 91%
“…Modules were connected to the motherboard, and the SMART-Chip was washed with 0.5% BSA/PBS (0.1 mL, 20 μL/min) prior to blood infusion. Stained cells were spiked into healthy blood and hydrodynamically introduced (1 mL, 25 μL/min) into the CTC selection module that was surface-decorated with anti-EpCAM monoclonal antibodies via a photocleavable (PC) linker . Following blood infusion, the module was rinsed with 1 mL of 0.5% BSA/PBS (50 μL/min) to remove any nonspecifically bound material.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Soper and coworkers (41,42) have demonstrated that surface immobilized (coumarin-4-yl)methyl as photocleavable linker 42 can be used to capture and enrich clinically relevant liquid biopsy markers, that is, circulating tumor cells and extracellular vesicles, with an affinity agent such as an antibody, that is covalently attached to the photocleavable linker via its amino group, Scheme 10. Irradiation with blue LED light (412 nm) is used to cleave the long chain ester from the C-4 methyl of the coumarin to release the Ab-CTC or Ab-EV complexes in > 90% yields.…”
Section: Representative Applicationsmentioning
confidence: 99%